2010
DOI: 10.1016/j.jcrs.2010.04.042
|View full text |Cite
|
Sign up to set email alerts
|

Late dislocation of in-the-bag and out-of-the bag intraocular lenses: Ocular and surgical characteristics and time to lens repositioning

Abstract: The possible major predisposing factors for late IOL dislocation were PXF, glaucoma, and cataract surgery complicated by zonular dehiscence. Primary placement of the IOL in the ciliary sulcus was associated with earlier IOL dislocation. Intraocular lens repositioning surgery using a posterior or anterior approach was successful in many cases. FINANCIAL

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
101
4
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(112 citation statements)
references
References 28 publications
5
101
4
2
Order By: Relevance
“…Furthermore, IOL dislocation has been documented following irregular capsulorrhexis creation in the presence of zonular dialysis. 3,16 However, some evidence exists suggesting that CTR insertion will not exclusively prevent IOL dislocation. A total of 21 out of 84 (27%) in a study by Jakobsson et al, and 8 out of 45 (18%) in a study by Lorente et al had IOL dislocation following CTR insertion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, IOL dislocation has been documented following irregular capsulorrhexis creation in the presence of zonular dialysis. 3,16 However, some evidence exists suggesting that CTR insertion will not exclusively prevent IOL dislocation. A total of 21 out of 84 (27%) in a study by Jakobsson et al, and 8 out of 45 (18%) in a study by Lorente et al had IOL dislocation following CTR insertion.…”
Section: Discussionmentioning
confidence: 99%
“…Both of these studies had high frequencies of eyes with PPXF syndrome (60% and 66.7%, respectively). 16,17 Although this is likely to be a major risk factor for late IOL dislocation, the possibility of iatrogenic damage during, and mis-timing of CTR insertion, cannot be discounted. 8 In comparison, our study revealed that 8 patients with zonular dialysis had PXF, of whom 4 (50%) underwent CTR insertion during surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, in the other case series published to date, PEX was the most important risk factor. 1,6,8,23 Lorente et al, 7 in a recent study also performed in Spain, showed that PEX was found in 66.6% of the cases (30 eyes), whereas high myopia was only detected in 1 case (2.22%). This emphasizes that PEX incidence depends highly on the geographical location, even within a small country such as Spain.…”
Section: Postoperative Complicationsmentioning
confidence: 92%
“…The incidence of surgery specifically due to late dislocated IOL is 0.032-0.28%. 1,2 In a recent observational study, it was shown that the cumulative risk of IOL dislocation at 5, 10, 15, 20, and 25 years after cataract extraction was 0.1%, 0.1%, 0.2%, 0.7%, and 1.7% respectively. 3 Nevertheless, the pseudophakic population has been growing very quickly in recent years as a result of the longer lifespan, the new phacorefractive procedures, and the improvement in the quality and safety of phacoemulsification surgery.…”
Section: Introductionmentioning
confidence: 99%